Synthesis and characterization of biogenic zinc oxide nanoparticles photocatalysts and evaluation of its antioxidant, antibacterial and nanotoxicity properties - Lau, Gee Een (2021)
During the process of dyeing and printing in textile industry, more than 8000 chemicals are taking part. Methyl orange (MO) and Methylene blue (MB) are synthetic dyes commonly used in the dyeing process. Inappropriate usage and disposal of these synthetic dye may lead to negative impacts on the environment. Photocatalysis of nanoparticles is a pioneering wastewater treatment technique, notably for those containing organic compounds which are difficult to remove. The fascinating physical and chemical properties made zinc oxide nanoparticles (ZnONPs) famous in nanotechnology. The research highlights the potential of new nano-agents on antioxidant and photocatalytic activity. The roselle flower and oil palm leaf extracts act as reducing agents, while Sodium hydroxide (NaOH) is used as a precipitating agent during the synthesis of ZnONPs. Synthesis of ZnONPs without the addition of plant extracts, ZnO (B) was used as blank control of the study. Characterization and analytical studies were conducted on the synthesized ZnONPs. GC-MS discovered that saturated and unsaturated fatty acids were the main constituents in both extracts. EDX revealed the synthesized ZnONPs constituent two elements, Zn and O. The FTIR analysis showed the presence of phenolic compounds and Zn-O stretching bond in green synthesized products. In terms of morphology, the size of the synthesized ZnONPs was 10–15 nm. They are found in agglomerated spherical-shaped. XRD spectra revealed the ZnONPs have 20-30 nm crystallite size. ZnONPs have wurtzite structure in Raman spectrum. UV Vis discovered that ZnONPs have relatively large band gap, which are 2.9 eV and 3.2 eV. TGA proved high thermal stability of ZnONPs. ESR revealed the presence of oxygen vacancies in ZnONPs, which play a vital role in the dye degradation process. The presence of 5% of ZnONPs as catalysts under exposure of 10 W UV lamp could degrade 10 ppm MO in 5 hours and MB in 3 hours efficiently. ZnONPs exhibit high antioxidant and antibacterial properties, especially with the presence of phenolic compounds. Artemia sp.assay discovered that low toxicity of ZnONPs has the potential to work as water treatment agents. To conclude, for pharmaceutical and industry use, ZnONPs can be further developed.